Perencanaan Interaktif sebagai Perwujudan Pembangunan Berkelanjutan dalam Pengembangan Wilayah Permukiman di Kabupaten Sidoarjo - Evinda Fenny Wulandari; Anggraeny Puspaningtyas; Adi Soesiantoro (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
Population growth in Sidoarjo Regency has increased quite high every year. This then causes an increase in the need for land as residential land to meet the population’s housing needs. To overcome this problem, efforts are needed from the Sidoarjo Regency Government through development planning and development of residential areas. This research discusses the application of Interactive Planning in development planning and development of residential areas in Sidoarjo Regency as well as coordination between relevant stakeholders in developing residential areas in Sidoarjo Regency. The aim of this research is to determine the application of interactive planning in development planning in Sidoarjo Regency as well as the coordination carried out between stakeholders in implementing the development of residential areas in Sidoarjo Regency. The theory used in this research is the Interactive Planning theory put forward by Ackoff Russel. The Method used is a descriptive qualitative research method with data collection techniques through observation, interviews, and documentation. The results of this research are that the application of interactive planning in development planning and development residential areas in Sidoarjo Regency is already underway but hasn’t been implemented optimally. This is based on the success factors of interactive planning which include participative principal, continuity principal, and holistic principal which are still not optimally fulfilled. Apart from that, coordination between stakeholders in the implementation of residential area development is still not optimal.